Rancang Bangun Customer Relationship Management(CRM) Dalam Penjualan Berbasis E-Commerce - Syahnita, Syahnita; Nofriadi, Nofriadi; Sudarmin, Sudarmin (Forum Kerjasama Pendidikan Tinggi, 2022)
The development of the business world has entered a new era, where there are more and more new companies and competing companies in the service, trade, and manufacturing sectors. The higher the level of customer education, the customer will indirectly become critical and careful in making their choices. In a situation like this, the company must not only rely on the products it produces, but the company must also establish good relationships with each of its loyal customers so that customers will be loyal to the company. Umi Nala Shop Aneka Serbu is engaged in sales such as selling children's toys, household appliances and various types of gifts. The problems that occur at Umi Nala Shop Aneka Serbu are, the sales process at Umi Nala Shop Aneka Serbu is still doing conventional sales, there are no facilities that help customers to get information, submit an assessment of the product and also experience difficulties in processing and storing customer data. who have made buying and selling transactions, there is no facility for customers to submit complaints or product evaluations. This study utilizes CRM features that aim to help the service system at Umi Nala Shop Aneka Serbu to attract new customers and retain old customers and expand the sales system. This application is made using the PHP programming language and MySQL as the database server. With this system, it is hoped that the system of marketing, sales, service and utilization of Customer Relationship Management will have a positive influence on customer loyalty so that customers remain loyal to Umi Nala Shop Aneka Serbu